CRISPR/Cas9‐mediated knockout of an oil palm defense‐related gene to the pathogenic fungus Ganoderma boninense - Asmini Budiani; Imam Bagus Nugroho; Dini Astika Sari; Inez Palupi; Riza Arief Putranto (Universitas Gadjah Mada, 2019)
Oil palm plantation in Indonesia is significantly affected by basal stem rot disease caused by the pathogenic fungus Ganoderma boninense. Tolerant oil palm cultivars toward G. boninense have been developed through a breeding program accelerated by the implementation of the CRISPR/Cas9 technology. This study was conducted to perform a gene knockout (KO) of oil palm that confers a putative defense‐related trait toward G. boninense. A plasmid pCRISPR_EMLP containing modules, i.e., 35S‐CaMV‐promoter‐driven CRISPR/Cas9, U6‐promoter‐driven sgRNA to the target EgEMLP gene (EL695076), and hygromycin resistance gene as the selectable marker, was established for Agrobacterium‐mediated delivery into oil palm calli (OPC). The transformed OPCs were regenerated and screened in DF (de Fossard) media containing hygromycin. The working concentration of hygromycin was successfully optimized for selection at 20 ppm. Through PCR‐based selection using HYG primers, we succeeded in discerning positive transformed OPC clones. The sequenced PCR products of genomic DNA as the template amplified using EMLP1 primers showed a point mutation, causing a frameshift in the edited EgEMLP and premature stop codon. Furthermore, in silico modeling demonstrated that the mutation resulted in a change in the C‐terminal region, affecting the tertiary protein structure. Moreover, electrophoresis analysis of PCR products of cDNA as the template from transformed OPC clones showed several samples with faint or undetected bands. This indicated that the CRISPR/Cas9 module induced a mutation that could destabilize the transcribed mRNA, e.g., premature degradation. Altogether, this study has successfully implemented CRISPR/Cas9 gene editing in oil palm in a model gene that is responsible for putative defense‐related traits toward the pathogenic fungus G. boninense.